Preparation method of degradable medical brushite coating on magnesium alloy surface
The preparation of calcium permeable phosphite coatings through chemical deposition of the primary battery system solved the problem of fast degradation speed and insufficient biocompatibility in the bone repair field, and achieved a coating with strong binding force and high density, which delayed the coating. The degradation of magnesium alloys and enhances biocompatibility and osteoinduction capabilities.
Patent Information
- Application Number
- CN202411271189.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The application of existing medical magnesium alloys in the field of bone repair is due to the problem of its rapid degradation rate and insufficient biocompatibility, which leads to the loss of mechanical support of the implant and the excessive local magnesium ion concentration, which affects bone tissue healing, and existing calcium The preparation method of phosphorus coating is complicated, has high cost or has poor coating adhesion.
Using chemical deposition method based on the primary cell system, a coating with a two-layer structure of the bottom magnesium fluoride film and the outer magnesium permeable phosphite is formed by fluorination pretreatment and calcium permeable phosphite deposition, and a coating is formed by metal plates and magnesium alloy samples. The primary battery promotes the nucleation and deposition of calcium and phosphorus salts, and reduces the precipitation of hydrogen that affects the density of the coating.
It significantly improves the bioactivity and corrosion resistance of the surface of magnesium alloy, reduces the corrosion rate of the magnesium alloy matrix, obtains a calcium permeable phosphite coating with strong binding force and dense structure, delays the degradation rate of magnesium alloy, and improves the Biocompatibility and osteoinduction ability.
Smart Images

Figure CN119113200A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomaterials and provides a method for preparing a calcium-phosphorus coating on the surface of a medical magnesium alloy. Specifically, the method relates to a method for preparing a brushite coating on the surface of a degradable medical magnesium alloy for bone repair. Background Art
[0002] As one of the typical representatives of the new generation of degradable biomaterials, medical magnesium alloy materials have received widespread attention. Especially in the field of orthopedic implants, compared with traditional bone fixation materials such as stainless steel and titanium alloys, magnesium alloy materials can be completely degraded in the human body, avoiding secondary surgery for removal. At the same time, the magnesium ions released during the degradation process have a significant osteoinductive effect. A number of magnesium alloy bone implants have been clinically applied, including the MAGNEZIX hollow compression screw produced by Syntellix of Germany, which has obtained the European CE certification, and the K-MET screw produced by U&i of South Korea, which has obtained the Korean KFDA certification.
[0003] However, magnesium degrades quickly in the human body, which can cause the implant to lose mechanical support prematurely and even lead to surgical failure. At the same time, rapid degradation leads to excessive local magnesium ion concentration and gas accumulation around the implant, affecting bone tissue healing. The above problems severely limit the clinical application scope of medical magnesium alloys in the field of bone repair. Therefore, how to regulate the degradation rate of magnesium alloys to prevent them from losing the necessary mechanical integrity prematurely and further improve tissue compatibility is the biggest challenge they face.
[0004] Surface modification is a very effective means to improve the corrosion resistance and biocompatibility of medical magnesium alloy substrates. Among them, calcium-phosphorus coating has good bioactivity and osteoinductivity because of its composition similar to that of human bone tissue, and has become one of the important surface modification coatings in the field of magnesium alloys for bone repair. Calcium-phosphorus coatings mainly include brushite (DCPD), octacalcium phosphate (OCP), amorphous calcium phosphate (ACP), tricalcium phosphate (TCP) and hydroxyapatite (HA). Compared with other calcium-phosphorus phases, DCPD has a larger solubility, which can increase the concentration of calcium ions and phosphate ions near the implant and promote bone integration. Many in vitro studies have shown that DCPD has good biocompatibility for osteoblasts, fibroblasts and macrophages. Common preparation methods for calcium-phosphorus coatings on the surface of medical magnesium alloys include chemical conversion, anodizing, electrodeposition, sol-gel method, etc. The chemical conversion method is to form a film layer on the surface of the sample through a chemical reaction. The process is simple and the coating is well bonded. However, the film layer is thin and has general biocompatibility, and is often used as a pretreatment process for other coatings; the anodic oxidation method is to place the magnesium alloy as the anode in the electrolyte, and form an oxide film on the surface of the sample by loading a certain current. The obtained coating has the advantages of high hardness and good bonding strength. However, this method is complicated, the coating has many defects, is brittle, and some coatings are not easy to degrade; the electrochemical deposition method is to deposit ions in the solution on the surface of the sample under the action of an electric field. The coating prepared by this method is relatively uniform, but the bonding strength is general; the sol-gel method is to use a colloidal solution as a precursor to polymerize it on the surface of the magnesium alloy to form a three-dimensional mesh gel, and then dry and solidify it to form a coating. The coating has good biocompatibility, but the structure of the coating itself is relatively loose and the bonding strength is general. In summary, the development of a preparation method for calcium-phosphorus coatings with simple process, stable quality, uniform and dense coatings, and strong bonding strength is the key to its large-scale stable production and clinical transformation.
[0005] The existing public technology CN 115142026 B first uses the FCVA method (magnetic filtration cathode vacuum arc deposition) to prepare a pure magnesium film layer with a thickness of 3-5 μm on the surface of the magnesium alloy, and then immerses the sample in a mixed solution of calcium nitrate and phosphoric acid to obtain a calcium-phosphorus coating. The mixed solution used in the patent is highly acidic and highly corrosive to the substrate, so a pure magnesium intermediate layer with high purity needs to be prepared. The preparation method is complex and costly.
[0006] CN 102787339 A adopts an electrochemical deposition method, uses graphite as an anode, and a pretreated magnesium alloy substrate as a cathode, and prepares a calcium-phosphorus coating in a mixed electrolyte solution of calcium nitrate and diammonium phosphate. This method requires an external power supply and requires precise control of parameters such as current density, electrolyte composition, and temperature, which increases the complexity of the process and the difficulty of operation.
[0007] CN 103451640 A discloses a technology for preparing a calcium-phosphorus coating directly on the surface of a ZK60 magnesium alloy by a chemical conversion method. The conversion solution used is prepared from 0.01-0.2M sodium dihydrogen phosphate dihydrate and calcium nitrate tetrahydrate, and the coating is obtained after immersion for 5-100 hours. At present, there are still the following problems. First, the chemical conversion solution used in this process is strongly acidic, and while forming the coating, it will also cause the surface of the magnesium alloy to be severely damaged, which is manifested as cracks at the grain boundaries of the magnesium alloy. Secondly, during this reaction process, the surface of the magnesium alloy will quickly release hydrogen, which is not conducive to the deposition of calcium-phosphorus salts. Therefore, the coating prepared by this process has poor adhesion, which affects the durability and stability of the material as a whole.
[0008] Patent CN 102206819 B discloses a technology for preparing calcium-phosphorus coating with simple process and strong bonding strength. The specific process is that the magnesium-based alloy treated with fluoride is chemically converted in a mixed solution of calcium dihydrogen phosphate monohydrate, sodium nitrate and hydrogen peroxide to obtain a brushite coating. This method has the advantages of simple process and high coating bonding strength. However, the coating obtained by this process has a high roughness, especially when preparing a thinner coating, the coating may be uneven, affecting the corrosion resistance of the sample. Summary of the invention
[0009] The present invention aims at the deficiencies of the prior art and provides a method for preparing a degradable brushite coating on the surface of a medical magnesium alloy. This method can not only significantly improve the biological activity of the magnesium alloy surface, but also effectively reduce the corrosion rate of the magnesium alloy substrate. The preparation process of the invention is simple, and the coating prepared by the invention technology has strong bonding force, dense structure, good corrosion resistance and biocompatibility.
[0010] The objective of the present invention is achieved through the following technical solutions:
[0011] The present invention provides a method for preparing a calcium-phosphorus coating on the surface of a medical magnesium metal, wherein the calcium-phosphorus coating is a brushite coating, and the method comprises the following steps:
[0012] S1. Fluorination pretreatment: The magnesium or magnesium alloy sample is placed in a hydrofluoric acid solution and immersed at a constant temperature to form a fluoride film on its surface, and then taken out, cleaned, and blown dry;
[0013] S2. Brushite deposition: Brushite deposition: A metal plate with a chemical activity lower than that of magnesium and magnesium alloy is used as an anode, and the sample obtained in step S1 is used as a cathode. The anode and the cathode are connected with a conductor or directly contacted, and are placed together in a brushite deposition solution and immersed at a constant temperature to form a primary battery system, wherein:
[0014] Cathode reaction: Mg→Mg 2+ +2e,
[0015] Anode reaction: 2H2O+2e→2OH - +H2;
[0016] Then, the nucleation and deposition of calcium phosphate salts occur at the cathode to obtain a brushite coating.
[0017] As an embodiment of the present invention, the metal plate is a copper plate, a steel plate, a titanium plate or a zinc plate. The chemical activity of the four metal plates is lower than that of the magnesium alloy. The metal plate and the sample are connected or directly contacted with a conductor to form a galvanic cell, in which the metal plate serves as an anode and the magnesium alloy sample serves as a cathode.
[0018] The advantages of this device are: the hydrogen generated by the anode reaction can be precipitated from the metal plate instead of from the magnesium alloy sample, avoiding the influence of hydrogen precipitation on the coating deposition and coating density. At the same time, the galvanic cell reaction accelerates the reaction speed on the surface of the magnesium alloy sample, and is also conducive to promoting the nucleation and deposition of calcium phosphate salts, which is conducive to the grain refinement and roughness reduction of the calcium phosphate coating. Especially when the ratio of the surface area of the metal plate to the surface area of the magnesium or alloy sample is 2 to 20:1, the galvanic cell reaction speed and coating deposition speed are most suitable.
[0019] As an embodiment of the present invention, in step S1, the concentration of the hydrofluoric acid solution is 20-40%.
[0020] As an embodiment of the present invention, in step S1, the soaking temperature is room temperature and the soaking time is 6-48h. The time of hydrofluoric acid soaking will directly affect the formation of the magnesium fluoride layer. If the soaking time is too short, i.e., less than 6h, a complete and uniform magnesium fluoride layer may not be formed, resulting in a weak or unevenly distributed subsequent calcium phosphate coating; and if the soaking time is too long, the excessively thick magnesium fluoride layer formed may increase the interfacial stress between the coating and the substrate, affecting the bonding strength and stability of the coating.
[0021] As an embodiment of the present invention, the brushite deposition solution is a mixed solution of Ca(NO3)2, phosphate and H2O2 prepared in a certain proportion; the phosphate is at least one of NaH2PO4 and NH4H2PO4. Here, calcium phosphate is avoided as a component of the deposition solution directly because the solubility of calcium phosphate is often not large, which easily leads to premature precipitation of the deposition solution and a decrease in the ion concentration of the solution.
[0022] As an embodiment of the present invention, the calcium ion concentration in the brushite deposition solution is 0.1-0.25 mol / L, and the molar concentration percentage of calcium ions and phosphate ions is 1:0.8-1.2. If the molar concentration is greater than this range, that is, the phosphate ions are insufficient, the crystallinity of brushite in the coating may be reduced, the crystal structure is incomplete, thereby affecting the bonding force between the coating and the substrate, and the brushite may be converted into other types of calcium phosphate salts, such as hydroxyapatite, etc., thereby changing the expected chemical properties and structural properties of the coating; if the molar concentration is less than this range, a high concentration of phosphate ions may cause abnormal crystal structure or phase change in the coating, and accelerate the overall reaction rate, resulting in excessive crystal growth. As a result, the coating is unevenly distributed on the substrate, and then the thickness is uneven, affecting the corrosion resistance and stability of the coating as a whole.
[0023] As an embodiment of the present invention, the concentration of H2O2 added to the brushite deposition solution is 0.1-0.3 mol / L. Hydrogen peroxide has strong oxidizing properties. According to the reaction formula H2O2+2H + +2e - →2H2O, which can consume a large amount of hydrogen ions to generate water, thereby preventing hydrogen from precipitating on the surface of the magnesium alloy substrate, thereby affecting the bonding strength between the coating and the substrate. This concentration range has been verified by experiments and has passed the feasibility test. If the added hydrogen peroxide is higher than this concentration range, excessive hydrogen ion consumption will affect the solubility of calcium dihydrogen phosphate in the solution, slowing down the formation rate of the calcium-phosphorus coating; when the amount of hydrogen peroxide added is insufficient, the effect of consuming hydrogen ions is relatively limited, and the bonding strength between the coating and the substrate may still be affected by hydrogen precipitation.
[0024] As an embodiment of the present invention, in step S2, the calcium ion concentration and the phosphate ion concentration range are between 0.1-0.25 mol / L. If the concentration is too low, the reaction is difficult to proceed in the direction of generating DCPD (CaHPO4·2H2O), resulting in a thin coating thickness and insufficient corrosion resistance to protect the substrate. When the concentration is too high, the reaction rate of generating DCPD in the solution is greatly increased. In addition to being deposited on the substrate, a large amount of precipitation will also be generated in the solution, resulting in uneven growth of brushite grains and large differences in coating grain size, which in turn leads to a non-dense coating structure.
[0025] As an embodiment of the present invention, the preparation method of the brushite deposition solution is: weigh the required Ca(NO3)2 and phosphate, dissolve them in ultrapure water respectively, to prepare Ca(NO3)2 solution and phosphate solution; mix the solutions evenly, add H2O2 to the mixed solution, and adjust the volume to a certain volume to obtain the brushite deposition solution.
[0026] As an embodiment of the present invention, the constant temperature immersion in step S2 is 20-25° C., and the immersion time is 6-24 hours. The immersion time should not be too long, otherwise the DCPD coating will partially dissolve as the pH value of the conversion solution slowly increases.
[0027] As an embodiment of the present invention, the brushite coating obtained by the preparation method of the present invention has a two-layer structure. The bottom magnesium fluoride film layer has a thickness of 150nm-3μm, which can be used as a protective film on the surface of the magnesium alloy substrate to slow down the corrosion rate of the substrate and provide a platform for nucleation and growth of the biologically active calcium phosphate coating, thereby improving the bonding strength of the coating.
[0028] As an embodiment of the present invention, the outer layer is brushite (DCPD) with a thickness of 5 μm-20 μm; the surface has a rough morphology with lath-shaped grains.
[0029] As an embodiment of the present invention, the magnesium metal includes pure magnesium and magnesium alloys, and the magnesium alloys include magnesium alloy series such as Mg-Zn series, Mg-Ca series, Mg-Mn series, Mg-RE series, and a new medical magnesium alloy series designed to improve the performance of magnesium alloys.
[0030] The medical magnesium or magnesium alloy material with a penetrating calcium phosphate coating on the surface prepared by the method of the present invention, and its use as a bone repair material, also fall within the scope of protection of the present invention. The bone repair material includes an intrabone implant, specifically including bone plates, bone nails, bone tissue engineering scaffolds and other bone repair-related intrabone implants.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention adopts a chemical deposition method based on a galvanic cell system to prepare a brushite coating on the surface of a magnesium alloy sample, which includes a bottom magnesium fluoride film layer and an outer brushite two-layer structure, and the coating has a strong bonding force with the substrate. The coating obtained by the method of the present invention has high density, strong bonding force, significantly reduced roughness, and uniform and controllable thickness, which can not only slow down the degradation rate of the magnesium alloy substrate, but also further improve its biocompatibility and osteogenic ability.
[0033] 2. The present invention utilizes the galvanic cell reaction formed between the metal plate and the magnesium alloy sample to precipitate the hydrogen generated by the reaction from the anode metal plate, thereby preventing the precipitation of hydrogen from the surface of the magnesium alloy and affecting the coating deposition and coating density. At the same time, the galvanic cell reaction accelerates the cathode reaction rate on the surface of the magnesium alloy sample, and is also beneficial to promote the nucleation and deposition of calcium phosphate salts, which is beneficial to the grain refinement and roughness reduction of the calcium phosphate coating.
[0034] 3. The preparation method of the present invention has simple and stable process, low cost and high production efficiency, and can be applied to magnesium-based bone implant devices with complex shapes. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0036] Figure 1 This is the XRD diffraction pattern of the bioactive brushite (CaHPO4·2H2O) coating on the surface of the magnesium alloy prepared in Example 1.
[0037] Figure 2 The scanning electron microscope image of the bioactive brushite (CaHPO4·2H2O) coating on the surface of the magnesium alloy prepared in Example 1. The image shows that the brushite coating is evenly covered, presents fine apatite-like crystals, is dense, and has high bonding strength with the substrate. This morphology is very similar to the crystal characteristics of bone apatite, which is conducive to the deposition of bone in the body and has good biocompatibility.
[0038] Figure 3 This is a scanning electron microscope image of the bioactive brushite (CaHPO4·2H2O) coating on the surface of the magnesium alloy prepared in Comparative Example 1. The coating is composed of large lath-shaped grains and has a relatively large surface roughness. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0040] Example 1
[0041] The magnesium alloy matrix of the present embodiment is a Mg-Nd-Zn-Zr alloy disc. After the sample is cleaned, it is immersed in 40% hydrofluoric acid for 12 hours to form a dense MgF2 film layer on the sample surface, and its thickness is about 1.5μm (test method: the cross section of the sample with magnesium fluoride film formed on the surface is ground flat, and the coating area can be measured by observing the coating area under a scanning electron microscope). After taking it out, it is cleaned and dried with ultrapure water and absolute ethanol. Then, a Ca(NO3)2 aqueous solution and a NaH2PO4 aqueous solution are respectively configured, and a solution containing 0.125mol / L Ca(NO3)2 and 0.1mol / L NaH2PO4 is uniformly mixed to obtain a solution, and a certain volume of H2O2 (the final concentration of H2O2 is 0.1mol / L) is added to obtain a brushite deposition solution. A copper plate and a magnesium alloy sample were connected by a copper wire, the surface area ratio of the copper plate to the surface area of the magnesium alloy sample was 20:1, and they were immersed in the above-mentioned brushite deposition solution, and immersed in a water bath at a constant temperature (25°C) for 12 hours to obtain a brushite coating. The coating had a thickness of 8μm and a roughness Ra of 2.8μm. Figure 1 The XRD diffraction pattern of the prepared magnesium alloy surface coating shows that the coating composition is brushite (DCPD). Figure 2 The microscopic morphology of the coating on the surface of the magnesium alloy is dense and uniform. The results of the in vitro corrosion test show that the average degradation rate of the coating sample in Hank's simulated body fluid (immersed at 37°C for 20 days) is 0.15mm / year.
[0042] Coating thickness test method: embed the coating sample in resin, grind and polish the sample cross section, and observe and measure the coating thickness under a scanning electron microscope.
[0043] In vitro corrosion test method: Prepare magnesium alloy surface calcium-phosphorus coating samples (diameter 14mm, thickness 3mm), and configure Hank's simulated body fluid. Each sample is immersed in 200mL solution at 37℃ for 20 days, and hydrogen is collected with an inverted funnel and burette, and the amount of hydrogen precipitated is recorded, and then the corrosion rate of the magnesium alloy sample is calculated based on the amount of hydrogen.
[0044] Example 2
[0045] The magnesium alloy matrix used in this embodiment is WE43 (Mg-RE series) alloy fracture screw. After cleaning the sample, soak it in 40% hydrofluoric acid and shake it on a shaker for 12 hours. After taking it out, use ultrapure water and anhydrous ethanol to clean it and blow it dry to obtain a magnesium fluoride film with a thickness of about 1.2μm. Then, a Ca(NO3)2 aqueous solution and a NaH2PO4 aqueous solution are respectively prepared, mixed evenly to obtain a solution containing 0.2mol / L Ca(NO3)2 and 0.2mol / L NaH2PO4, and then a certain volume of H2O2 (the final concentration of H2O2 is 0.2mol / L) is added to obtain a calcium phosphate deposition solution. The magnesium alloy sample is placed on a steel plate, the ratio of the surface area of the steel plate to the surface area of the magnesium alloy sample is 5:1, and they are soaked in the above-mentioned calcium phosphate solution together, and soaked in a water bath at a constant temperature (25°C) for 24h to obtain a calcium phosphate coating. The coating thickness is 12μm and the roughness Ra is 3.2μm.
[0046] Example 3
[0047] The magnesium alloy matrix used in this embodiment is a ZK60 (Mg-Zn series) alloy bone plate. After the sample is cleaned, it is soaked in 30% hydrofluoric acid for 8 hours, washed with ultrapure water and anhydrous ethanol in turn, and dried to obtain a magnesium fluoride film with a thickness of about 1.2μm. Then, a Ca(NO3)2 aqueous solution and an NH4H2PO4 aqueous solution are respectively prepared, mixed evenly to obtain a solution containing 0.2mol / L Ca(NO3)2 and 0.24mol / L NH4H2PO4, and then a certain volume of H2O2 (the final concentration of H2O2 is 0.3mol / L) is added to obtain a brushite deposition solution. A titanium plate is connected to the magnesium alloy sample using titanium wire, and the ratio of the surface area of the titanium plate to the surface area of the magnesium alloy sample is 2:1. They are soaked in the above-mentioned calcium-phosphorus solution together, and soaked in a water bath at a constant temperature (25°C) for 48h to obtain a brushite coating. The coating thickness is 20μm and the roughness Ra is 3.8μm. The biocompatibility of the calcium phosphate coating prepared in this example was evaluated using MC3T3-E1 osteoblasts. The osteoblast activity was over 90%, and the cytotoxicity was at level 0-1, meeting the basic requirements for in vivo implants.
[0048] Example 4
[0049] The magnesium matrix used in this embodiment is a high-purity magnesium (99.99wt.%) porous bone tissue engineering scaffold (porosity 75%, average pore size 700μm). After the sample is cleaned, it is soaked in 20% hydrofluoric acid and shaken for 6 hours using a shaking table. After taking it out, it is cleaned and dried with ultrapure water and anhydrous ethanol to obtain a magnesium fluoride film with a thickness of about 1μm. Then, a Ca(NO3)2 aqueous solution and an NH4H2PO4 aqueous solution are respectively configured, mixed evenly to obtain a solution containing 0.15mol / L Ca(NO3)2 and 0.15mol / LNH4H2PO4, and then a certain volume of H2O2 (the final concentration of H2O2 is 0.2mol / L) is added to obtain a calcium phosphate deposition solution. The porous magnesium scaffold sample is placed on a zinc plate, the ratio of the zinc plate surface area to the magnesium alloy sample surface area is 10:1, and is immersed in the above-mentioned calcium phosphate solution together, and is immersed in a water bath at a constant temperature (25°C) for 6h to obtain a calcium phosphate coating. The coating has a thickness of 5 μm and a roughness Ra of 2.9 μm. The coating significantly improves the biocompatibility of the porous magnesium scaffold sample, raising its cytotoxicity from level 3 without coating to level 1. Moreover, after coating, the porous magnesium scaffold still maintains a three-dimensional interconnected pore structure, and the coating is well bonded to the substrate.
[0050] Comparative Example 1
[0051] The preparation method of this comparative example is basically the same as that of Example 1, except that the magnesium alloy sample is not connected to the copper plate, that is, there is no metal plate as the anode, so a stable primary battery system cannot be formed, hydrogen will be precipitated on the magnesium alloy sample, and the calcium and phosphorus deposition rate on the surface of the magnesium alloy is slow, resulting in increased coating roughness and reduced density. Figure 3 The microscopic morphology of the calcium-phosphorus coating obtained in Comparative Example 1 is shown in FIG. 1 . The coating thickness is 9 μm and the roughness Ra is 8.4 μm. Figure 3 It can be seen that the coating is composed of large lath-shaped grains.
[0052] Comparative Example 2
[0053] The preparation method of this comparative example is basically the same as that of Example 1, except that the ratio of the surface area of the metal plate to the surface area of the magnesium alloy sample is 1:1, that is, the surface area of the metal plate is relatively small, which will lead to a slow cathode reaction rate, and at the same time, slow down the nucleation speed and deposition speed of the coating on the magnesium alloy sample, resulting in increased coating roughness and reduced density. The coating thickness is 8.6μm and the roughness Ra is 6.5μm.
[0054] Comparative Example 3
[0055] The preparation method of this comparative example is basically the same as that of Example 1, except that the ratio of the surface area of the metal plate to the surface area of the magnesium alloy sample is 30:1, that is, the surface area of the metal plate is too large compared to the surface area of the magnesium alloy sample, at this time, the reaction rate of the primary cell is too fast, and the calcium-phosphorus deposition rate on the surface of the cathode magnesium alloy sample is too fast, which is not conducive to forming a dense and uniform coating. The coating thickness is 35μm and the roughness Ra is 9.5μm.
[0056] Comparative Example 4
[0057] The preparation method of this comparative example is basically the same as that of Example 1, except that the solution components are changed to 0.2mol / L Ca(NO3)2·4H2O, 0.1mol / L NaH2PO4·2H2O, and 0.1mol / LH2O2 in the step of preparing the brushite conversion solution, the molar concentration percentage of calcium ions and phosphate ions in the solution is 2:1, and the prepared calcium-phosphorus coating has a calcium-phosphorus atomic ratio of 1.3:1, indicating that in addition to brushite, other types of calcium phosphate salts are also converted on the magnesium alloy substrate. At the same time, the bonding force between the coating and the substrate is weak, which may be due to the reduced crystallinity of brushite in the coating, thereby affecting the bonding force between the coating and the substrate.
[0058] Comparative Example 5
[0059] This comparative example adopts the method of preparing magnesium alloy-calcium-phosphorus coating composite material by electrochemical deposition in CN 102787339 A, that is, 150mL of electrolyte solution containing 0.1M Ca(NO3)2·4H2O, 0.06M NH4H2PO4, 30% H2O2 15mL / L, pH value of 4 is prepared, the pretreated Mg-Nd-Zn-Zr alloy disc substrate is used as cathode, graphite is used as anode, and the calcium-phosphorus coating obtained by the above method is deposited in a water bath at 20°C environment for 2h at a current of 1-2mA and a voltage of 4V. Compared with the coating obtained in Example 1, the roughness and density are poorer. The reason may be that in the electrochemical deposition process, slight fluctuations in process parameters (such as changes in current) may lead to significant changes in the surface roughness of the coating. This instability makes it difficult to control the roughness of the coating; at the same time, impurities in the electrolyte (such as undissolved solid particles, bubbles, etc.) are easily attached to the surface of the coating, affecting the density of the coating.
[0060] Comparative Example 6
[0061] In this comparative example, the coating is directly prepared on the surface of the ZK60 magnesium alloy by the chemical deposition method in CN 103451640 A, that is, after removing the oxide layer on the surface of the magnesium alloy with sandpaper, the magnesium alloy is cleaned and dried, and then directly immersed in a conversion solution, wherein the conversion solution used is prepared from 0.01M sodium dihydrogen phosphate dihydrate and calcium nitrate tetrahydrate, and the calcium-phosphorus coating can be obtained by immersing for 24 hours. Compared with the coating obtained in Example 1, the calcium-phosphorus coating obtained by the above method is significantly thinner, so that it is easy to peel off or fall off when subjected to external force; and because the magnesium alloy quickly produces hydrogen in the acidic conversion solution during the immersion process, the coating is not tightly bonded to the substrate, and the long-term corrosion resistance of the coating is poor.
[0062] Comparative Example 7
[0063] The preparation method of this comparative example is basically the same as that of Example 1, except that the solution composition is changed to the formula in CN 102206819 B in the step of preparing the brushite conversion solution, that is, the sample is placed in a solution of NaNO3: Na3PO4: Ca(H2PO4)2·H2O: H2O2 = 2:2:5:1 (wt%) and immersed in a water bath at a constant temperature for 48 hours. The obtained coating has the same macroscopic morphology as Example 1, but the surface is relatively rougher. Under a scanning electron microscope, there are problems of large differences in crystal particle size and non-dense coating structure. In addition, the Ca(H2PO4)2·H2O added to the conversion solution has a low solubility and is easily precipitated on the surface, affecting the coating quality.
[0064] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a calcium-phosphorus coating on the surface of medical magnesium metal, characterized in that: The calcium-phosphorus coating is a brushite coating, and the method comprises the following steps: S1. Fluorination pretreatment: The magnesium or magnesium alloy sample is placed in a hydrofluoric acid solution and immersed at a constant temperature to form a fluoride film on its surface, and then taken out, cleaned, and blown dry; S2, brushite deposition: A metal plate with a chemical activity lower than that of magnesium and magnesium alloy is used as an anode, and the sample obtained in step S1 is used as a cathode. The anode and the cathode are connected with a conductor or directly contacted, and are placed together in a brushite deposition solution and immersed at a constant temperature to form a galvanic cell system, wherein: Cathode reaction: Mg→Mg 2+ +2e, Anode reaction: 2H2O+2e→2OH - +H2; Then, the nucleation and deposition of calcium phosphate salts occur at the cathode to obtain a brushite coating.
2. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 1, characterized in that: The brushite deposition solution is a mixed solution of Ca(NO3)2, phosphate and H2O2 prepared in a certain proportion; the phosphate is at least one of NaH2PO4 and NH4H2PO4; the calcium ion concentration in the brushite deposition solution is 0.1-0.25 mol / L, the molar concentration percentage of calcium ions and phosphate ions is 1:0.8-1.2, and the added concentration of H2O2 is 0.1-0.3 mol / L.
3. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 2, characterized in that: The preparation method of the brushite deposition solution is as follows: weigh the required Ca(NO3)2 and phosphate, dissolve them in ultrapure water respectively, to prepare a Ca(NO3)2 solution and a phosphate solution; mix the solutions evenly, add H2O2 to the mixed solution, and adjust the volume to a certain volume to obtain the brushite deposition solution.
4. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 1, characterized in that: The metal plate is a copper plate, a steel plate, a titanium plate or a zinc plate; the ratio of the surface area of the metal plate to the surface area of the magnesium or magnesium alloy sample is 2 to 20:
1.
5. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 1, characterized in that: In step S1, the concentration of the hydrofluoric acid solution is 20-40%, the immersion temperature is room temperature, and the immersion time is 6-48 hours.
6. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 1, characterized in that: The constant temperature soaking in step S2 is 20-25° C., and the soaking time is 6-24 hours.
7. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 1, characterized in that: The thickness of the fluoride film is 150nm-3μm, and the thickness of the brushite coating is 5μm-20μm.
8. The method for preparing a calcium-phosphorus coating on a surface of medical magnesium metal according to claim 1, characterized in that: The magnesium alloy includes at least one of Mg-Zn series, Mg-Ca series, Mg-Mn series, and Mg-RE series medical magnesium alloys.
9. A medical magnesium or magnesium alloy material having a brushite coating on its surface, prepared by the method according to any one of claims 1 to 8.
10. Use of the medical magnesium or magnesium alloy material according to claim 9 as a bone repair material.
Citation Information
Patent Citations
Method for preparing bioactive calcium phosphate coating on magnesium alloy surface for endosseous implant
CN102206819B
Method for preparing magnesium alloy - calcium phosphorus coating composite material by electrochemical deposition
CN102787339A
Method for preparing degradable biomedical magnesium alloy / calcium-phosphorus coating composite material
CN103451640A
A method for obtaining a dense calcium phosphate coating on a magnesium alloy surface
CN115142026B
